The prophylactic effects of nigella sativa and thymoquinone against cyclophosphamide toxicity on reproductive capacity and embryo development in mice - Saheera binti Kamarzaman (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2014)
Advances in the treatment of cancer have allowed adolescent patients to become long-term survivors able to lead normal lives. However, the concern about the effects of anticancer drugs on fertility has led to many efforts to preserve germ cells of these patients. This study focuses on ways to assess the effectiveness of Nigella sativa and its active compound, thymoquinone, in lowering chemotherapeutic-associated toxicity of cyclophosphamide on the ovaries and testes of Balb/c mice. Histological and morphological effects on the germ cells were examined via microscopy techniques and possible fragmentations of sperm DNA was assessed using the COMET Assay. The RNA expression of OGG1 and FGF2 in the testicular cells was quantitatively analysed using the real-time PCR followed by quantification of the stages of fertilisation and embryo division using the inverted microscope. Supplementation of N. Sativa oil and thymoquinone exhibited noticeable protective effects on the histology and morphometry of the ovaries and seminiferous tubules as well as being effective in reducing the total DNA fragmentation in spermatozoa. N. Sativa extract reduced the percentage of abnormal sperm head post to cyclophosphamide treatment and preserved the normal chromatin condensation indicative of protection against sperm DNA alteration. The expressions of DNA repair and fibroblast growth factor genes were also shown to increase suggestive of possible reduction in mutagenic modifications. Thymoquinone supplementation increased the implantation and fertilisation rates, pregnancy outcome as well as preserved fair quality embryos following paternal and maternal exposures to cyclophosphamide. N. Sativa and thymoquinone are both suitable exogenous agents that offer viable chemoprotective potential against toxicity induced by cyclophosphamide. This study is part of an effort towards improving interventions to preserve fertility and to assist in the development of techniques in achieving favourable reproductive outcomes for adults who survived childhood cancer following chemotherapy.